The effect of nanomicelle curcumin supplementation and Nigella sativa oil on the expression level of miRNA‐21, miRNA‐422a, and miRNA‐503 gene in postmenopausal women with low bone mass density: A randomized, triple‐blind, placebo‐controlled clinical trial with factorial design. (8th September 2021) - Farshbaf‐Khalili, Azizeh; Farajnia, Safar; Pourzeinali, Samira; Shakouri, Seyed Kazem; Salehi‐Pourmehr, Hanieh
Abstract : This study aimed to investigate the effect of nanomicelle curcumin (CUR), Nigella sativa oil (NS), and CUR and NS on the plasma levels of miR‐21, miR‐422a, and miR‐503 expression in postmenopausal women with low bone mass density (BMD). This randomized, triple‐blind, placebo‐controlled clinical trial with a factorial design was conducted on 120 postmenopausal women from the integrated healthcare system, Tabriz‐Iran. The BMD was determined using dual‐energy X‐ray absorptiometry (DEXA). Women were randomly divided into four groups of 30 participants: (a) CUR (80 mg) and placebo of NS, (b) NS (1, 000 mg) and placebo of CUR, (c) CUR (80 mg) and NS (1, 000 mg), and (d) both placebos (containing microcrystalline cellulose). The plasma level of miRNA‐21, miRNA‐422a, and miRNA‐503 was determined by qRT‐PCR. The expression level of miRNAs at the baseline was similar. At the end of the intervention, only the expression level of miRNA‐21 changed statistically significantly between the four groups ( p  = .037) and between the NS and placebo groups ( p  = .005). Also, its expression in the two groups receiving NS ( p  = .037) and NS–CUR ( p  = .043) was significantly increased. NS and NS–CUR supplementation can increase the expression level of miRNA‐21 in postmenopausal women with low bone density, and bring perspective to further studies of the target.